Analisis Penerapan Sistem Informasi Pelayanan Online Administrasi Kependudukan DINDUKCAPIL Banyumas di Kecamatan Kemranjen (Current Research in Education: Conference Series Journal, 2023)
Currently the development of the era is increasingly advanced, almost all human activities that are done manually can be helped by sophisticated information and communication system technology. As with population data collection in Kemranjen District, which is now assisted by the population administration online service information system created by the Banyumas Regency Population and Civil Registration Service (DINDUKCAPIL) for its citizens with the aim of helping to overcome the spread of the covid-19 virus. This study aims to find out how the application of the Banyumas DINDUKCAPIL Population Administration Online Service Information System in Kemranjen District and look for weaknesses in the function and appearance of the website. The method used is descriptive qualitative and in obtaining data using interview, observation, and documentation techniques. The results of this study are expected to be able to invite residents in the Kemranjen sub-district in particular to use this application and also the website admin can develop this information system to make it more comfortable to use.